KEMERDEKAAN PERS PADA ORDE REFORMASI - Muhammad Syahnan Harahap (JURNAL ILMIAH HUKUM DIRGANTARA, 2019)
The freedom of the press in the reform remains based on article 28 of the 1945 Constitution. Just as the old order and the new order. The demand of the reform order is independence or freedom. The upholding of human rights in this case is freedom to voice opinions or feelings through the press media. Still its implementation depends on the political system and legislation that develops in the country including those concerning the responsibility of the press it self.Key words : independence, pers, order of reform